Evaluation of specific heavy metal levels of pregnant women complicated by neural tube defects (Annals of Medical Research, 2021)
Aim: The etiology of neural tube defect (NTD) is still not clear enough. In our study, we aimed to evaluate plasma heavy metal levels of pregnant women with NTD and to determine whether there is a relationship between heavy metal levels and NTD severity.Material and Methods: TThis study was conducted in Adıyaman University, Department of Gynaecology and Obstetrics. The study included 38 pregnant women with NTD and 42 pregnant women with healthy infants. Pregnant women who have NTD were divided into two groups as NTD Type 1 and NTD Type 2 according to the anomaly type. Levels of heavy metals such as Mercury (Hg), Cadmium (Cd), Cobalt (Co), Lead (Pb), Manganese (Mn) and Arsenic (As) were compared between groups.Results: Plasma Hg, Co, Cd and Pb levels were higher in NTD group than control group. (p values, respectively; p 0.001, p = 0.001, p 0.001, p 0.001). As and Mn levels were not statistically different between the two groups (p values; p = .519, p = .819, respectively). In the NTD group, Hg was found to be higher in NTD Type 1 than NTD Type 2 (p 0.001).Conclusion: It is obvious that some histomorphological changes are formed in the cardinal ligaments of patients with uterine prolapse due to pressure on the uterus. We believe that the increase in the number of extravasated erythrocytes and the thickness of the vascular wall and peripheral nerve should be supported by further studies.
Keywords: Anencephaly; heavy metal; neural tube defect; pregnancy; spina bifida